Propargyl 1,2-orthoesters as glycosyl donors: stereoselective synthesis of 1,2-trans glycosides and disaccharides - Sureshkumar, Gopalsamy; Hotha, Srinivas (Tetrahedron Letters, 2007)
Propargyl 1,2-orthoesters are identified as glycosyl donors. Various glycosides and disaccharides were synthesized in a stereoselective manner using AuBr3 as the promoter. AuBr3 may activate the alkyne resulting in the formation of a 1,2-dioxolenium ion and also behaves as a Lewis acid to facilitate the attack of the glycosyl acceptor. The versatility of the protocol was demonstrated using a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols. (C) 2007 Elsevier Ltd. All rights reserved.